Effect of replacement therapy (CRRT) and hemodialysis (IHD) on severe acute renal failure - Zhang, Xiangyuan; Yuan, Yinfang (Frontiers in Pharmacology, 2023)
Severe acute renal failure (SARF) is more common in clinical practice and has a high mortality rate. Acute renal failure can be divided into three stages: oliguria, polyuria, and recovery. Hyperkalemia, metabolic acidosis and acute uremia are the main symptoms in patients with severe acute renal failure. The clinical symptoms are obvious and endanger the life and health of the patient, which requires active and effective measures to be treated. To investigate the efficacy of alternative therapies and hemodialysis in the treatment of severe acute renal failure, data samples were randomly divided into observation and control groups. The control groups and observation groups were given conventional treatment and hemodialysis and substitution therapy, respectively. Clinical data has showed that there was an improvement in the parathyroid hormone, renin content and quality of life in patients with severe acute renal failure in the observation groups after substitution therapy and hemodialysis treatment. The improvement rate was 9.47%, which had certain promotion value.